A first step toward understanding patient safety - Kyoung Ok Kim (Korean Journal of Anesthesiology, 2016)
Patient safety has become an important policy agenda in healthcare systems since publication of the 1999 report entitled "To Err Is Human." The paradigm has changed from blaming the individual for the error to identifying the weakness in the system that led to the adverse events. Anesthesia is one of the first healthcare specialties to adopt techniques and lessons from the aviation industry. The widespread use of simulation programs and the application of human factors engineering to clinical practice are the influences of the aviation industry. Despite holding relatively advanced medical technology and comparable safety records, the Korean health industry has little understanding of the systems approach to patient safety. Because implementation of the existing system and program requires time, dedication, and financial support, the Korean healthcare industry is in urgent need of developing patient safety policies and putting them into practice to improve patient safety before it is too late.